Analogous programming with a template class library - Gregorics, Tibor (Teaching Mathematics and Computer Science, 2012)
In this paper, a template class library and its usage can be read. The classes of the library contain the C++ code of the algorithm of programming theorems. This library supports the implementation of the programs that are planned by analogous programming but the primary aim of its usage is to introduce the object-oriented programming style to show how a reusable code can be written with inheritances, overriding virtual methods, composition of objectcs and template parameters.